2010
DOI: 10.1186/1758-3284-2-36
|View full text |Cite
|
Sign up to set email alerts
|

p53 in head and neck cancer: Functional consequences and environmental implications of TP53mutations

Abstract: BackgroundAlthough TP53 mutations in human tumours generally have been extensively studied, the significance of p53 in the aetiology of head and neck cancers is still incompletely characterized. In recent years, considerable interest has been focused on mutant forms of p53, the abnormal protein product of TP53 alleles with missense mutation that often accumulate in cancer cells.MethodsWe compared the nature of TP53 mutations in primary 46 head and neck squamous cell carcinomas (HNSCC) analyzed by PCR-SSCP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 50 publications
2
30
1
3
Order By: Relevance
“…HNCisamultifactorialdiseaseforwhichepidemiological evidence suggests HPV infection to be an etiological factor. Severalotherenvironmentalfactors,suchastobaccosmoking andalcoholconsumption,havealsobeenshowntobeassociated with the development of HNC [14][15][16]. Although our overall meta-analysis provided some evidence of an associationbetweenMDM2SNP309T/GandHNCrisk(OR=0.82, 95%CI0.67-0.99forTGvs.GG),inconsiderationoftheresultsofthesubgroupanalysis,theMDM2309T/Ggenotype decreasedtheHNCriskmainlyintheNPCsubgroup.Therefore, the results of the overall meta-analysis must be interpretedcautiously.Onelimitationofourmeta-analysisisthe lack of detailed individual data such as lifestyle.…”
Section: Discussionmentioning
confidence: 60%
“…HNCisamultifactorialdiseaseforwhichepidemiological evidence suggests HPV infection to be an etiological factor. Severalotherenvironmentalfactors,suchastobaccosmoking andalcoholconsumption,havealsobeenshowntobeassociated with the development of HNC [14][15][16]. Although our overall meta-analysis provided some evidence of an associationbetweenMDM2SNP309T/GandHNCrisk(OR=0.82, 95%CI0.67-0.99forTGvs.GG),inconsiderationoftheresultsofthesubgroupanalysis,theMDM2309T/Ggenotype decreasedtheHNCriskmainlyintheNPCsubgroup.Therefore, the results of the overall meta-analysis must be interpretedcautiously.Onelimitationofourmeta-analysisisthe lack of detailed individual data such as lifestyle.…”
Section: Discussionmentioning
confidence: 60%
“…In one study, the researchers found a concomitant reduction in ABCC1 mRNA levels with wtp53 expression (8). Previous reports suggested that a functional polymorphism in codon 72 of p53 gene, which encodes polyproline domain with a vital role in apoptosis induction, is in relation to the most cancers (18)(19)(20)(21)(22)(23) and prevalence of exon 5-8 mutations, which encodes the DNA binding domain of the TP53 molecule are found in many of human cancers (5,26). On the other hand, a report by Zhao et al, indicated that promoter polymorphism of ABCC1 gene too, is associated with cancer development (10).…”
Section: Discussionmentioning
confidence: 99%
“…For example, previous studies have demonstrated that a variety of environmental pollutants could cause the genetic mutation or functional disability of p53 (Anetor, 2012;Besaratinia and Pfeifer, 2010;Peltonen et al, 2010), which is a most important tumor suppressor. Our preliminary data also identified a crucial role of iron in stabilizing p53 via an interaction with ferritin.…”
Section: Discussionmentioning
confidence: 99%